Evaluation of the Relationship Between Arterial Blood Pressure, Aortic Stiffness and Serum Endothelin-1 Levels in Patients with Essential Hypertension. (December 2013) - Nar, Gokay; Soylu, Korhan; Akcay, Murat; Gulel, Okan; Yuksel, Serkan; Meric, Murat; Zengin, Halit; Erbay, Aliriza; Nar, Rukiye; Demircan, Sabri; Sahin, Mahmut
Abstract : This study has attempted to evaluate the relationship between aortic stiffness, blood pressure (BP) and serum endothelin-1 (ET-1) levels in patients with essential HT. Totally 152 subjects, consisting of 103 patients diagnosed with HT at least 1 year previously and 49 healthy individuals, were enrolled in this study. They were subdivided, on the basis of BP measurements made at home, into three groups as the hypertensives with dysregulated BP ( n = 56), the hypertensives with regulated BP ( n = 47) and the normotensive controls ( n = 49). Statistically significant differences were observed between the three groups with respect to aortic elasticity parameters ( p < 0.01 for aortic strain, aortic distensibility and aortic stiffness). Serum ET-1 levels in the three groups were similar ( p = 0.101), but a significant correlation was observed between the ET-1 values and the aortic elasticity parameters ( p = 0.004). Alteration of the aortic elasticity parameters in patients with HT not only correlates with the serum ET-1 levels indicating endothelial dysfunction but also gives direct clues about status of BP regulation.